Creative Dance of Ban Wang Khong’s Wisdom of Making Flowers from Rubber Leaf Fibers - Changsan, Teerawat (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The objectives of this research and development were to 1) study the knowledge and wisdom of making flowers from rubber leaf fibers of the Ban Wang Khong enterprise group, and 2) create a dance from the knowledge and wisdom found. Samples to collect the knowledge of rubber leaf fibers were 8 academics, 2 professional choreographers, and 6 local experts. The samples to create the dance were 11 students from Performing Arts Program, Nakhon Si Thammarat Rajabhat University and 50 audience to assess the dance satisfaction. The structured in-depth interviews, participant observation, and questionnaire were used to collect data and they were analyzed content analysis and descriptive statistics. The results revealed that the wisdom in making handicrafts using rubber leaf fibers could be choreographed into a new dance following four steps of flowers crafting; harvesting, fermenting, bleaching and bunching. The dance was deployed into twelve different styles of movements and directions. Twenty dance patterns were divided into 4 portions regarding melody of accompanying music. The dance costumes were designed respectably to the villagers’ ways of life and their dressing styles by adding body and hair accessories. Three types of artificial props using rubber leaves were created; lamps, flow trays, and wreath to reflects uniqueness of the South. The accompanying music is a combination of Nang Talung (Shadow Play) and Ligay Pa (Musical Folk Drama) that reflects the identity of Southern music. Satisfaction assessments showed that the audience were satisfied at the highest level in 7 items; props (mean 4.69), reflection of cultural performances and community lifestyles, and crafting career (mean 4.64, 4.63), props and accessories can be used for product development (mean 4.61), music reflected the Southern identity (mean 4.60, the dance could be performed in any occasion (Mean 4.60) and the dance could promote community economic value (mean of 4.56).